2007
DOI: 10.1093/humrep/dem149
|View full text |Cite
|
Sign up to set email alerts
|

Expression of angiogenic factors in endometriosis: relationship to fibrinolytic and metalloproteinase systems

Abstract: Endometrium and peritoneal fluid from women with endometriosis have increased levels of VEGF, uPA and MMP-3 levels. Therefore, the development of endometriotic implants at ectopic sites may be facilitated, promoting the progress of the endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
82
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 49 publications
12
82
0
2
Order By: Relevance
“…The establishment of ectopic sites of endometrial growth is an invasive event linked, among other things, to altered expression of MMPs. Gilabert-Estellés et al [17] showed that the mRNA expression of MMP-3 was significantly higher in the endometrium of women with endometriosis than in controls, confirming previous reports [27,28,29,30]. Our data indicate that the mRNA level of MMP-3 was significantly higher in peripheral blood from endometriotic women than from control samples.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The establishment of ectopic sites of endometrial growth is an invasive event linked, among other things, to altered expression of MMPs. Gilabert-Estellés et al [17] showed that the mRNA expression of MMP-3 was significantly higher in the endometrium of women with endometriosis than in controls, confirming previous reports [27,28,29,30]. Our data indicate that the mRNA level of MMP-3 was significantly higher in peripheral blood from endometriotic women than from control samples.…”
Section: Discussionsupporting
confidence: 91%
“…Vascular endothelial growth factor (VEGF) is the primary stimulus for angiogenesis, and it increases vessel permeability in endometriosis [11,12,13,14]. Previous studies have indicated a significant increase in VEGF and its mRNA expression in endometriotic lesions compared to controls or eutopic endometrium [15,16,17,18,19]. Contradictory results have been reported concerning peripheral blood levels of VEGF in women with or without endometriosis; some published data reported higher levels in cases of endometriosis [20,21,22,23], while other data reported no differences at all [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The information presented in one review [35] suggest that the functional activity of the cytokine family, which includes, in addition to TGF beta proteins, morphogenesis of bone, under the direct control of the sex steroids are directly involved in the regulation of such key exchange processes in the tissues of the uterus, including the management of cyclical proliferation and apoptosis in epithelial repair processes, angiogenesis and local modulation of immune responses. In addition to the direct effect of TGF beta in the formation of new blood vessels [39,40], the effect of the cytokine on the physiological and pathophysiological mechanisms of neoangiogenesis in uterine tissues can be realized through the regulation of collagen metabolism, which includes a number of metalloproteinases and their tissue inhibitors [41]. On the one hand, the results of their research provide evidence of activation of sodium chloride TGF beta, as evidenced by the maximum intensity of tissue fibrosis, sclerosis of blood vessels, neoangiogenesis and adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…The human VEGF gene (VEGFA, OMIM 192240) is located on chromosome 6p12 (Zhao Z, et al 2008). VEGF messenger ribonucleic acid and protein were significantly higher in women with endometriosis, which supported a key role for VEGF in the pathological angiogenesis in endometriosis (Gilabert-Estelles J, 2007). In particular several transcription factor-binding sites are found in the VEGF 5' -untranslated region and variation within the region increases the transcriptional activity.…”
Section: Genetic Polymorphisms Of Vegf Genesmentioning
confidence: 90%